The obstacle is the way - Holiday, Ryan. (New York : Portfolio/Penguin, 2014)
"A guide not just for overcoming the obstacles that hold us back-but for using them for great benefit The great Athenian orator Demosthenes was born with a crippling speech impediment and was robbed of his inheritance by cruel guardians. Samuel Zemurray was a poor roadside fruit peddler pitted against the behemoth United Fruit Company. Ulysses S. Grant found himself stuck across the Mississippi river, desperately trying to break into the impenetrable fortress of Vicksburg. These icons and many others throughout history-from John D. Rockefeller to Amelia Earhart to Richard Wright to Steve Jobs-were often placed in nearly impossible situations that turned out to be the platforms for astounding triumphs. They were not exceptionally brilliant, lucky, or gifted. Their success in overcoming extreme obstacles was the result of a timeless set of philosophical principles that great men and women have always followed. Now Ryan Holiday unpacks those lessons and reframes them for today's world, building on the wisdom of the ancient Stoics and a rich trove of examples. He shows us how to turn obstacles into advantages, through controlling our perceptions, swift and energetic action, and true force of will"--
"A guide to overcoming adversity by drawing on the wisdom of the ancient Stoics"--
Includes bibliographical references.
Keywords: BUSINESS & ECONOMICS / Motivational; PHILOSOPHY / General; Motivation (Psychology); Self-realization.